Anesthetic Considerations in Pediatric Patients With Acute Decompensated Heart Failure. (March 2022) - Sebastian, Roby; Ullah, Sana; Motta, Pablo; Das, Bibhuti; Zabala, Luis
Acute decompensated heart failure (ADHF) in pediatrics is a significant cause for morbidity and mortality in children. Congenital heart disease and cardiomyopathy are the leading etiologies of ADHF. It is common for these children to undergo diagnostic, therapeutic, or surgical procedure under anesthesia, which may be associated with significant morbidity and mortality. The importance of preanesthetic multidisciplinary planning with all involved teams, including anesthesia, cardiology, intensive care, perfusion, and cardiac surgery, cannot be emphasized enough. In order to safely manage these patients, it is imperative for the anesthesiologist to understand the complex pathophysiological interactions between cardiopulmonary systems and anesthesia during these procedures. This review discusses the etiology, pathophysiology, clinical manifestations, and perioperative management of these patients.